Assessment of ferroptosis as a promising candidate for metastatic uveal melanoma treatment and prognostication - Swords, Ellie; Kennedy, Breandán N.; Tonelotto, Valentina (Frontiers in Pharmacology, 2024)
Uveal melanoma (UM) is the most common primary intraocular tumour in adults. Local resection, radiation therapy, and enucleation are the current first-line, primary UM treatments. However, regardless of the treatment received, around 50% of UM patients will develop metastatic disease within five to 7 years. In the largest published series of unselected patients with metastatic UM (mUM), the median survival time after diagnosis of metastasis was 3.6 months, with less than 1% of patients surviving beyond 5 years. Approved drugs for treatment of mUM include systemic treatment with tebentafusp-tebn or isolated hepatic perfusion (IHP) with melphalan. However, these drugs are only available to a subset of patients and improve survival by only a few months, highlighting the urgent need for new mUM treatments. Accurately predicting which patients are at high risk for metastases is also crucial. Researchers are developing gene expression signatures in primary UM to create reliable prognostic models aimed at improving patient follow-up and treatment strategies. In this review we discuss the evidence supporting ferroptosis, a non-apoptotic form of cell death, as a potential novel treatment target and prognosticator for UM.